Non-Ohmic and dielectric properties of a Ca2Cu2Ti4O12 polycrystalline system - Ramirez, M. A.; Bueno, Paulo Roberto [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (American Institute of Physics (AIP), 2006)
An investigation was made into the non-Ohmic and dielectric properties of a Ca2Cu2Ti4O12 perovskite-type system. Compared to the traditional CaCu3Ti4O12-based composition, the imbalance between the Ca and Cu atoms caused the formation of a polycrystalline system presenting similar to 33.3 mol % of CaCu3Ti4O12 (traditional composition) and similar to 66.7 mol % of CaTiO3. As for non-Ohmic properties, the effect of this Ca and Cu atom imbalance was that a nonlinear electric behavior of similar to 1500 was obtained. This high nonlinear electrical behavior emerged in detriment to the ultrahigh dielectric property frequently reported. The high non-Ohmic property was explained by the existence of Schottky-type barriers, whose formation mechanism may be similar to that proposed for traditional metal oxide non-Ohmic devices, according to similarities discussed herein. (c) 2006 American Institute of Physics.